A thirty months clinical evaluation of a posterior composite resin in primary molars - Cunha, Robson Frederico [UNESP] (My University, 2000)
The purpose of this in vivo study was to evaluate the clinical performance of a posterior composite resin TRH (Caulk Dentisply) in class I restorations in primary molars. A total of 30 children aged 5 to 8 years old with 49 class I dental lesions in primary molars participated in the study. The cavity preparations involved removal of carious lesion only and the enamel margins were beveled. The results showed after 30 months that, 82% (32/39) of Alfa ratings and 18% (7/39) of Bravo ratings. We concluded that the composite resin TP-H could be used in conservative restorations in primary molars, particularly in the late mixed dentition.
Keywords: resin; TPH hybrid; child; clinical trial; deciduous tooth; dental surgery; female; human; longitudinal study; male; methodology; molar tooth; preschool child; Child; Child, Preschool; Composite Resins; Dental Restoration, Permanent; Female; Humans; Longitudinal Studies; Male; Molar; Tooth, Deciduous